Expression of the growth hormone secretagogue receptor in pituitary adenomas and other neuroendocrine tumors. - Korbonits, M; Jacobs, R; Aylwin, S; Burrin, J; Dahia, P; Monson, J; Honegger, J; Fahlbush, R; Trainer, P; Chew, S; Besser, G; Grossman, AB (1998)
Synthetic GH secretagogues (GHSs; GH-releasing peptides and their nonpeptide mimetics) stimulate GH release, activate the hypothalamo-pituitary-adrenal axis, and release PRL in vivo. Patients with acromegaly show an exuberant GH response to GHSs, whereas patients with pituitary-dependent ACTH-secreting tumors show an exaggerated rise in ACTH and cortisol. We, therefore, studied the presence of GHS receptor (GHS-R) messenger ribonucleic acid (RNA) in 38 human pituitary tumors of different cell types, 3 ectopic ACTH-secreting tumors, a pancreatic gastrinoma, 3 insulinomas, and a non-secreting thymic carcinoid as well as in 7 normal pituitary glands. Certain pituitary tumors were also studied by in vitro cell culture with measurement of secreted GH, ACTH, PRL, FSH, LH, alpha-subunit, and TSH. RNA was extracted from tissue samples and, after RT, a duplex PCR reaction with primers for the GHS-R gene and for the housekeeping gene glyceraldehyde-3-phosphate dehydrogenase was performed, allowing semiquantitation of GHS-R expression. All the somatotroph adenomas (n = 8) showed a 2-10 times higher expression of the GHS-R gene compared to normal pituitaries. Higher than normal expression was shown in 5 of 18 tumors from patients with ACTH-secreting pituitary adenomas and in 1 of 3 ectopic ACTH-secreting carcinoid tumors. Two of the pituitary ACTH-secreting adenoma samples showed completely absent expression of the GHS-R, 8 showed expression similar to that of normal pituitary tissue, and 3 of the corticotroph adenoma tissue samples and 2 ectopic ACTH-secreting tumors showed a very low level of expression. One of 4 prolactinoma samples showed a high level of expression, 1 showed expression similar to that of normal pituitary, and 2 samples showed a very low level of expression. Nonfunctioning pituitary adenoma samples showed either absent or very low level expression of the GHS-R. The pancreatic gastrinoma sample showed expression similar to that of normal pituitary tissue, whereas 3 insulinomas showed low level expression of the GHS-R gene; a nonsecreting thymic carcinoid tumor showed no detectable expression. In summary, although GHS-R messenger RNA is abundant in human somatotroph adenomas, it is also present in other pituitary adenomas, particularly ACTH-secreting tumors. These findings may explain the in vivo responses to GHSs in patients harboring such tumors. It also appears from our study that GHS-R may be expressed in other neuroendocrine tumors.